Analisis Perbandingan Biaya dan Waktu Bekisting Kalsiboard dan Bata Ringan pada Pile Cap dengan Pendekatan BIM Revit (Studi Kasus : Proyek Kawasan IT Center BRI Ragunan Paket 1, Jakarta Selatan) - Diyan Selasih; Bambang Sugiyarto (Universitas Negeri Semarang, 2026)
This study aims to analyze the comparison of cost efficiency and work duration of Pile Cap formwork using calcium silicate board (Kalsiboard) and lightweight BRIck materials at the IT Area BRI Ragunan Project. The research method applies Building Information Modeling (BIM) using Autodesk Revit to generate accurate formwork material Material Takeoff based on construction drawings. The quantity data obtained from Revit are then used as the basis for calculating material costs and work durations by referring to labor coefficients from the Indonesian Standard Unit Price Analysis (AHSP). The results show that the use of calcium silicate board formwork is more efficient than lightweight BRIck formwork in terms of both material cost and construction time. The total duration of Pile Cap formwork work using calcium silicate board is 28.5 days, while the use of lightweight BRIck requires 47.5 days. This difference is influenced by material characteristics and installation methods, as calcium silicate boards are lighter and easier to install, resulting in higher labor productivity. Based on the analysis, it can be concluded that calcium silicate board formwork is a more efficient and feasible alternative for Pile Cap construction. However, proper material handling and management are required to minimize the risk of damage during transportation and installation. The results of this study are expected to serve as a reference for selecting formwork materials in similar construction projects.